Impact of nurse staffing coverage and care complexity factors on health outcomes in hospitalized COVID-19 patients: a cross-sectional study - Jordi Adamuz; Maribel González-Samartino; Emilio Jiménez-Martínez; Marta Tapia-Pérez; María-Magdalena López-Jiménez; Patricia Valero-Valdelvira; Esperanza Zuriguel-Pérez; Carmen Berbis-Morelló; Susana Asensio-Flores; Maria-Eulàlia Juvé-Udina (BMC Nursing)
Abstract Background Few studies have captured the impact of inadequate nurse staffing levels and broader health patient conditions in admitted patients during the COVID-19 pandemic. We aimed to determine the association between nurse staffing coverage, care complexity individual factors (CCIFs) and adverse events (AEs) in patients admitted with COVID-19. Methods A multicentre cross-sectional study was conducted from March 1, 2020 to March 31, 2022 at eight public health hospitals in Spain. All patients with COVID-19 who were admitted to these hospitals were included. The main variables included AEs, nurse staffing coverage (as measured using the ATIC patient classification system) and CCIFs to evaluate broader patient health conditions. Adjusted logistic models were performed to identify associations with AEs, stratified by patients admitted to wards and hospitalized patients who required admission to intensive care units (ICUs). Results A total of 11,968 hospitalized patients, 2,824 (23.6%) experienced AEs. Multivariate analysis showed that higher levels of nurse staffing coverage protected against AEs. Among patients admitted to acute wards, the independent risk factors for AEs included old age, haemodynamic instability, chronic disease, uncontrolled pain, urinary or faecal incontinence and mental status impairments. In addition to these factors, extreme weight, position impairment and communication disorders were factors associated with AEs in patients who required ICU admission. Conclusions Nurse staffing coverage was a protective factor for AEs. Several CCIFs related to comorbidity/complications, developmental, and mental-cognitive domains were strongly associated with AEs. Therefore, ensuring safe nurse staffing levels could be improve patient outcomes.